Membangun Budaya Religius Nusantara dalam Perspektif Islam - Bariki, Yusril; Dedi Rohayana, Ade; Muhtarom, Ali; Nila Khoirun Naili; Ahmad Nasyrul Ulum (Center for Research and Development of Religious Literature and Heritage, 2024)
Indonesia, with its diverse population, religions, ethnicities, and cultures, faces complex challenges in terms of religious harmony. This research examines the process of fostering religious harmony in village communities, which builds sociological wisdom, as practiced in Kasimpar village, Central Java. Using a qualitative approach, data were collected through observation, interviews, and documentation. The analysis employs Soerjono Soekanto's legal awareness theory. The findings reveal that the culture of tolerance practiced by the people of Kasimpar Village, characterized by high levels of ethnic, cultural, and religious plurality, is guided by the Kenambai Umbai philosophy (One heart, whole cheerful, work, achieve glory). This local wisdom has become the village's motto. The theoretical analysis shows that at the legal knowledge stage, the community recognizes that religious tolerance is not a differentiator among humans, but rather a matter of belief. At the legal understanding stage, the community understands that religious differences do not create sectarian divides. At the legal attitude stage, these differences foster mutual help and respect during worship. Finally, at the legal behavior stage, these differences enhance societal harmony, indicating that the people of Kasimpar Village have achieved legal awareness.